PENGABDIAN KEPADA MASYARAKAT DENGAN KULIAH KERJA NYATA (KKN) DI DESA MULYASARI KECAMATAN PANDIH BATU KABUPATEN PULANG PISAU - Dwi Yanti Fransiska Tumanggor; Evi Faridawat; Yongki Sabja; Christin A Simatupang; Arisa Elentina; Fajar Maulana Abdi; Christin, Christin; Jeanifer Oldy Noky; Maharani Dewi Dasi; Apriliana, Apriliana; Friskilla Wulandari; Gabriel Natasya Claudia; Alpin Hidayat; Recal Prasetyo; Deonalson, Deonalson (Bajang Institute, 2025)
KKN is a mandatory program in higher education that provides students with the opportunity to apply their theories to real-world community work. This initiative aims to enhance the community's understanding of health and education. The flagship program conducted during the first phase of KKN (July 16 – August 18, 2025) includes teaching programs at SDN Pangkoh Sari 3 and SDN Pangkoh Sari 4, health education for adolescents (Posyandu Remaja), and tutoring programs. The methods used in implementing the activities include observation, interviews, and focus group discussions. The results of the program indicate an improvement in students' understanding, adolescents' awareness of reproductive and mental health, and children's basic skills. It is hoped that this KKN program will have a broader and more sustainable impact on the community of Mulyasari Village.